Les plantations climatiques au Québec : Entre quantification de la nature et engagement socio-écologique - Giroux-Works, Nakeyah (Anthropologica, 2025)
Voluntary carbon offset markets based on forestry projects are very popular globally. However, they are met with scepticism and criticism on several fronts. Social science studies associate them with environmental injustices, such as land grabbing, restricting access to forest resources and placing the onus on southern countries to preserve the planet’s “green lungs.” What about when tree planting projects are conducted in northern regions such as Quebec in order to offset the emissions of people in these regions? Should we raise the alarm about these initiatives? This article takes a critical look at climatic plantations carried out within the confines of markets and environmental areas in Eastern Quebec, with the objective of evaluating and better understanding the benefits of carbon offsetting and trees planted for this purpose in civilian society.